2018
DOI: 10.1016/j.joen.2017.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of New Pulp-capping Materials NeoMTA Plus, MTA Repair HP, and Biodentine on Human Dental Pulp Stem Cells

Abstract: The new pulp-capping materials MTA Repair HP, NeoMTA Plus, and Biodentine showed a suitable degree of cytocompatibility with hDPSCs, and good cell migration rates, although Biodentine showed higher rates of proliferation time-dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
1
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(133 citation statements)
references
References 31 publications
8
113
1
11
Order By: Relevance
“…Biodentine is a novel bioceramic calcium silicate-based cement that possesses biocompatible and noncytotoxic properties [22,27]. In one study, the highest migration rate of dental pulp stem cells was found in the Biodentine group, and scanning electron microscopy revealed superior cell adhesion on disks of Biodentine [22].…”
Section: Discussionmentioning
confidence: 99%
“…Biodentine is a novel bioceramic calcium silicate-based cement that possesses biocompatible and noncytotoxic properties [22,27]. In one study, the highest migration rate of dental pulp stem cells was found in the Biodentine group, and scanning electron microscopy revealed superior cell adhesion on disks of Biodentine [22].…”
Section: Discussionmentioning
confidence: 99%
“…Alternation in material characteristics has recently led to development of new generation MTA-based cements; namely, Neo MTA Plus (Avalon Biomed Inc., Houston, TX, USA) and the iRoot (Innovative BioCeramix Inc., Vancouver, BC, Canada) products family. Both materials share the same clinical applications in vital pulp treatment, but only a few studies are available to assess their use in clinical practice [89][90][91][92]. Neo MTA Plus was developed to be used in pulpotomies without the risk of discoloration due to elimination of bismuth oxide.…”
Section: Novel Mineral Trioxide Aggregate Restorative Cementsmentioning
confidence: 99%
“…, Tomas‐Catala et al . ). They also promote reparative dentine formation, cementum formation and osteoblast differentiation (Koh et al .…”
Section: External Repair With or Without Endodontic Treatmentmentioning
confidence: 97%
“…An indirect or direct pulp cap using a bioactive endodontic cement such as Biodentine, (Biodentine TM Septodont, Saint-Maur-des-fosses, France) or MTA (ProRoot MTA, Dentsply Sirona Endodontics, Tulsa, OK, USA; MTA-Angelus, Angelus, Londrina-PR, Brazil) may be indicated if the pulp is close to being or is perforated, for example, Patel class 1Ap, 2Ap, 2Bp (Nair et al 2008, Nowicka et al 2013). These materials have excellent sealing ability , Koubi et al 2012, Raskin et al 2012, Ramezanali et al 2017, antibacterial properties ) and biocompatibility (Sultana et al 2018, Tomas-Catala et al 2018. They also promote reparative dentine formation, cementum formation and osteoblast differentiation (Koh et al 1997, Zanini et al 2012).…”
Section: External Repair With or Without Endodontic Treatmentmentioning
confidence: 99%